DEVELOPMENT OF INTERACTIVE MULTIMEDIA TOWARDS ECONOMIC PROBLEMS ON ECONOMIC SUBJECTS FOR SOCIAL SCIENCE CLASS X STUDENTS AT DARMA YUDHA HIGH SCHOOL - Sahala Freddy Simanjuntak (International Journal of Educational Best Practices, 2019)
This research aims to produce interactive multimedia using Lectora inspire in learning economic using the 4D development model. This work employed a qualitative descriptive method. Interactive multimedia was produced through three stages: definition, design, and development. This research was limited to the development stage. Definition stage comprised the preliminary analysis, curriculum analysis, material analysis, characteristic analysis, and formulation. Meanwhile, the design stage included pre-production from flowchart and storyboard making, media production to final activities: mixing, editing, and finalization. The development stage encompassed the following: (1) Expert appraisal, which was expert validation and revision with a result of very appropriate based on validation of media expert, material expert and language expert, and (2) Developmental testing, consisting of a small-scale tryout with a score of 81.98% (very appropriate). Our proposed system was very appropriate, according to the result of validation by an expert in a small-scale try-out; thus it can be used in economic learning at SMA Darma Yudha.